Pengembangan Media Diorama pada Pembelajaran Tematik Tema Ekosistem di Kelas V SD Putra Bangsa Berbudi - Batubara, Widia Putriana; Juwita, Putri (LPPM UMN Al Washliyah, 2025)
This research aims to develop diorama media with an ecosystem theme that is suitable for use in thematic learning on the theme